Analisis Studi Kelayakan Bisnis Pada Bank Syariah Indonesia KC Malang Ditinjau Dari Segi Aspek Lingkungan - Kurniawati, Lina (Maliki Interdisciplinary Journal, 2025)
The purpose of this research is to analyze the feasibility of a PT Bank Syariah Indonesia business in one of the Malang city branch offices, namely BSI Suprapto. The research method used in this research is using descriptive qualitative approach method. The results showed that BSI Malang Branch is feasible in environmental aspects.